If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3y = 1b Solving 4 + 3y = 1b Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3y = -4 + 1b Combine like terms: 4 + -4 = 0 0 + 3y = -4 + 1b 3y = -4 + 1b Divide each side by '3'. y = -1.333333333 + 0.3333333333b Simplifying y = -1.333333333 + 0.3333333333b
| 8(4.8-x)=22.4 | | 4x-12=1x+9 | | 2x-1+5x=-15 | | 4-3y=52 | | 3.8x-4.1=3.3x | | -(5x-6)=1 | | -20=-4/7x | | 1/2=25/x | | 360=85+93+107 | | 3=2y-1/4 | | 7(2x+8)=70 | | y=14-6y | | (8-3i)^2/(4-5i) | | 2a+192=30 | | 14v=6v+64 | | (8-3i)^2/4-4i | | 9.96=6.8 | | 121=(x+22) | | 596y-3.08=0.9y | | 0.1x^2+71x+100=0 | | -2p=-22 | | 4m+mp+3p+mp= | | 1.596y-3.0=0.9y | | 7=91/w | | (2x-47)+(x+2)=180 | | 18.35=2.7y | | 3x-2(3-2x)=18 | | s^3-5s^2-8s+40= | | -11p=44 | | -4+7=17 | | m+3=s+15-p | | 8x+7=7x+11 |